MONITORING AND CONTROLLING MARINE ACTIVITY USING IOT SYSTEM - Talib, Muhamad Lazim; Thanakodi, Suresh; Mat Noor, Norsheeda; Abdul Wahab, Norshahriah; Ahmad Fadzlah, Amalina Farhi; Nordin, Nur Hazimah (Malaysian Journal of Computer Science, 2021)
Marine activities at sea are very popular with the people of the world. Various marine activities such as swimming, boating, fishing and even shipping are often done on the coast and sea. However, loose control and monitoring cause various problems such as accidents, marine life threats and even pollution. The current method uses a vessel monitoring system (VMS) as well as a geographic information system (GIS). This method of course uses high costs because the information obtained is international. There are also barriers to obtaining sensitive information. This makes it difficult for local authorities to obtain uniform information on centralized water activities. This study proposes a smart and centralized system of control and monitoring of water activities. The novelty of this study is to recognise and detect a foreign object on the surface of the sea. In addition, this study made a virtual barrier between safe and dangerous zone. This system can control all marine activities with the use of mobile equipment installed on the body of the user or even the vessel used. The system will control and monitor all activities centrally. In the event of an emergency or violation of the law, this system will deliver an immediate message to the authorities. The system is evaluated based on user distribution and control environment. System performance audit shows that this system method successfully controls and monitors water activity within 1 kilometre from the coast